2016
DOI: 10.4088/pcc.15m01902
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Positive Psychological Intervention for Patients With Type 2 Diabetes

Abstract: ClinicalTrials.gov identifier: NCT02736084.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 45 publications
1
58
0
Order By: Relevance
“…Previous research with other populations indicates that interventions can increase optimism [29]. A small pilot study (N=15) of a positive psychological intervention for adults with Type 2 diabetes reported increased optimism, but additional research in larger samples is needed [30]. In addition to the outcomes supported by our findings (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…Previous research with other populations indicates that interventions can increase optimism [29]. A small pilot study (N=15) of a positive psychological intervention for adults with Type 2 diabetes reported increased optimism, but additional research in larger samples is needed [30]. In addition to the outcomes supported by our findings (i.e.…”
Section: Discussionsupporting
confidence: 68%
“…Three out of four PP studies measured positive affect, with only one finding significant improvement (with small effect size)[44]. The constructs of optimism and gratitude were also measured in one study (which did not test for significance)[43]. Otherwise, depression was measured in three of four PP studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among the two controlled studies, depression significantly changed in only one that examined the efficacy of an online, self-paced PP intervention [41]. Anxiety was measured in two studies; however, only one used a control group, and it found no statistically significant changes in anxiety [43]. Numerous other psychological outcomes were measured in the PP studies (see Tables 1 and 2) including perceived stress, confidence, and emotion, none of which showed statistically significant changes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an increasing number of positive psychology interventions that are aimed specifically at boosting positive emotions, optimism, altruism and overall well-being have now been implemented in medical populations [54][55][56][57][58][59]. These have been very well-accepted by participants and have been found to improve well-being and mental health in patients with HIV [55,57], asthma [60] and Type 2 diabetes [54,61]. In patients with heart disease, these programs have also been linked to greater well-being, less depression and improved health-related quality of life [62,63].…”
Section: Interventions To Promote Positive Psychological Well-beingmentioning
confidence: 99%